2021
DOI: 10.1021/acs.analchem.1c01978
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rofecoxib-Based Fluorescent Probes and Investigations on Their Solvatochromism, AIE Activity, Mechanochromism, and COX-2-Targeted Bioimaging

Abstract: Cyclooxygenase-2 (COX-2) fluorescent probes are promising tools for early cancer diagnosis. Traditionally, COX-2 probes were designed by connecting two parts, a fluorophore and a COX-2 binding unit, via a flexible linker. Herein, a new class of COX-2-specific fluorescent probes have been developed by one-step modification from rofecoxib by an integrative approach to combining the fluorophore and binding units into one. Among them, several new rofecoxib analogues not only retained their COX-2 binding ability bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…To gain insight into the mechanism of these photophysical properties from regioisomerization, density functional theory (DFT) calculations were carried out for the frontier molecular orbitals, including the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of PYR2 and PYR4 at the B3LYP/6‐311++G(d,p) level in DMSO (Figure 1c, d) [42,49] . Both compounds had similar frontier molecular orbitals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To gain insight into the mechanism of these photophysical properties from regioisomerization, density functional theory (DFT) calculations were carried out for the frontier molecular orbitals, including the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of PYR2 and PYR4 at the B3LYP/6‐311++G(d,p) level in DMSO (Figure 1c, d) [42,49] . Both compounds had similar frontier molecular orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that similar pattens for both PYR2 and PYR4 were observed for absorption and emission spectra in different solvents, although the magnitudes in intensity varied. The absorption bands at about 350 nm may be attributed to the π‐π* transition, and the weak ones at around 400 nm were ascribed to ICT transition [42] . When the solvent polarity was increased gradually from low polarity in chloroform (λ em =628 nm) to high polarity in DMSO (λ em =704 nm), the emission of PYR2 exhibited a red shift and the intensity gradually weakened, which was mainly due to the non‐radiative decay in polar solvents [52,53] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, AIEgen probes have been synthesized for the detection and imaging of other enzymes such as lipase [ 106 , 107 ], fucosidase [ 108 ], cyclooxygenase-2 (COX-2) [ 109 ] and β-N-acetylhexosaminidase (Hex) [ 110 ]. For example, lipase plays an important role in industrial catalysis, drug discovery and disease diagnosis; two AIEgens have been designed and used for the detection of lipase, including TPE and benzophenone derivatives [ 106 , 107 ].…”
Section: Othersmentioning
confidence: 99%